2022
DOI: 10.1021/acsami.2c12449
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Achieving Colossal Permittivity, Ultralow Dielectric Loss Tangent, and High Insulation Resistivity in Er-Doped SrTiO3 Ceramics via Oxygen Vacancy Regulation

Abstract: High-performance Sr1–x Er x TiO3 (x = 0–0.014) ceramics were sintered in different atmospheres using the conventional solid-state reaction method. The phase structure and micromorphology of ceramics were analyzed using X-ray diffraction and scanning electron microscopy. Meanwhile, the Sr1–x Er x TiO3 (when x = 0.012) ceramic sintered in hydrogen attains a colossal permittivity (132 543 @1 kHz, 157 650 @1 MHz) and ultralow tan δ (0.009 @1 kHz, 0.03 @1 MHz) and has good frequency stability (20 Hz to 2 MHz) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 70 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…Therefore, the relaxation behavior for the ceramic mainly arises from the migration of oxygen vacancies in grain boundaries. 29 We also used the formula 2πfτ = 1 to calculate the average relaxation time τ of ceramics, 30 which was based on the Z′∼Z″ curves obtained at 500 °C, 550 °C, and 600 °C and the results are shown in Fig. 7f.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the relaxation behavior for the ceramic mainly arises from the migration of oxygen vacancies in grain boundaries. 29 We also used the formula 2πfτ = 1 to calculate the average relaxation time τ of ceramics, 30 which was based on the Z′∼Z″ curves obtained at 500 °C, 550 °C, and 600 °C and the results are shown in Fig. 7f.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 depicts the frequency dependence of ε r and tan δ under different sintering atmospheres. The permittivity under different sintering atmospheres is significantly varied, indicating that the change in sintering atmosphere not only affects the polarization characteristics of the ceramics but also leads to a significant change in the polarization 38 . The essential factor that distinguishes the different atmospheres is the concentration of normalVnormalO${\mathrm V}_{\mathrm O}^{\centerdot \centerdot }$ in the ceramic samples, which illustrates the importance of normalVnormalO${\mathrm V}_{\mathrm O}^{\centerdot \centerdot }$ in the generation of CP behavior 38–40 .…”
Section: Resultsmentioning
confidence: 99%
“…The BTA0.015 ceramics sintered in N 2 not only have one to two orders of magnitude higher dielectric constants than other ceramics, but also have the lowest dielectric loss. It is suggested that the sharp increase in ε r is due to the promotion of large amounts of normalVnormalO${\mathrm V}_{\mathrm O}^{\centerdot \centerdot }$ in the high‐temperature anoxic environment, where free electrons are formed in parallel with normalVnormalO${\mathrm V}_{\mathrm O}^{\centerdot \centerdot }$ production 38 . The concentration of point defects and coupling into defect clusters varies due to the different content of Al 3+ ions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations